2008
DOI: 10.1158/0008-5472.can-07-5032
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 and CDK4 Activity Contribute to the Undifferentiated Phenotype in Neuroblastoma

Abstract: Genomic aberrations of Cyclin D1 (CCND1), CDK4, and CDK6 in neuroblastoma indicate that dysregulation of the G 1 entry checkpoint is an important cell cycle aberration in this pediatric tumor. Here, we report that analysis of Affymetrix expression data of primary neuroblastic tumors shows an extensive overexpression of Cyclin D1, which correlates with histologic subgroups. Immunohistochemical analysis showed overexpression of Cyclin D1 in neuroblasts and low Cyclin D1 expression in all cell types in ganglioneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
126
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 26 publications
16
126
0
1
Order By: Relevance
“…We also showed that knockdown of CND1 reproduces part of the phenotype observed by inhibition of the NFkB signaling. In good agreement with our findings, CND1 knockdown in neuroblasts promoted a reduction in cell proliferation and an extensive neuronal differentiation (Molenaar et al, 2008). 1 and 2), and a scrambled shRNA-negative control (lane 3), along with an EGFP-containing vector.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also showed that knockdown of CND1 reproduces part of the phenotype observed by inhibition of the NFkB signaling. In good agreement with our findings, CND1 knockdown in neuroblasts promoted a reduction in cell proliferation and an extensive neuronal differentiation (Molenaar et al, 2008). 1 and 2), and a scrambled shRNA-negative control (lane 3), along with an EGFP-containing vector.…”
Section: Discussionsupporting
confidence: 91%
“…CND1 has been suggested to maintain an undifferentiated phenotype of neuroblasts (Molenaar et al, 2008). As this gene was consistently upregulated in differentiated cells (Figure 1e), we evaluated its contribution to the NFkB-mediated control of differentiating GICs.…”
Section: Downmodulation Of Nfkb Activity Accelerates Maturation Of DImentioning
confidence: 99%
“…Upon mitogenic stimulation pRb functional inactivation is promoted through sequential phosphorylation by cyclin D-CDK4/6 and cyclin E-CDK2 complexes and results in the release of active E2F1-3 transcription factors capable of inducing the expression of genes encoding proteins crucial for the G1 to S phase transition [41,42]. In neuroblastoma cells cyclin D1 and CDK4 overexpression has been reported to play a role in pRb inactivation [30]. In this study, we show that in imatinib treated cells pRb phosphorylation at the CDK2-specific Thr-821 and CDK4-specific Ser-780 was decreased and in parallel the expression of two E2F responsive genes previously reported to be upregulated in neuroblastoma cells: SKP2 and cyclin A [30,31] was downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the effects of imatinib on CDK4 activity, the phosphorylation status of pRb at the CDK4-specific Ser-780 [30] was investigated. As shown in Fig.…”
Section: Exposure To Imatinib Downregulates the Expression Of Skp2 Anmentioning
confidence: 99%
See 1 more Smart Citation